The outcome of fractures of the proximal humerus after hemiarthroplasty - Jacobs, Leslie (My University, 2017)
Study design: This is a prospective clinical audit of patient data. Objectives: to determine the clinical outcomes in patients who have undergone hemiarthroplasty surgery of the shoulder. Background: Hemiarthroplasty of the shoulder involves the replacement of the humeral head in patients with fractures of the proximal humerus deemed too severe to fix. It is done routinely at Helen Joseph Hospital. Methods: Our study cohort consisted of 32 patients who had undergone hemiarthroplasty surgery for proximal humerus fractures over a period of four years from 2009 to 2013. All patients were assessed for the following: • The amount of pain they are experiencing in the operated shoulder • Whether their pain post fracture resolved with the surgery • How their activities of daily living are affected • Any functional impairment they are experiencing in the operated shoulder The data that was obtained from the patients included age, gender, Disabilities of Arm, Shoulder and Hand (DASH) score1 and range of motion of both the operated shoulder and the unoperated shoulder. Data was first captured using Microsoft Excel and then Stata 13.0 was used to perform the analysis. Results: Of the 32 patients that participated in the study, there were 12 males and 20 females. The mean age of the patients was 70.5 years (range 51 – 84 years). The mean DASH score was 36.9 (range 18.3 – 53.3). The DASH scores were positively correlated with the ages of the patients. The active range of motion of the operated shoulder was compared to the opposite shoulder in each patient. The range of motion was assessed according to flexion, extension, abduction, internal rotation and external rotation. In each of the 5 movements, the degree of movement in the operated shoulder was less than in the opposite shoulder, which had not been previously operated on. These differences were statistically significant p <0.001. Conclusion: Hemiarthroplasty remains a viable option for the treatment of patients with proximal humerus fractures that are deemed too severe to repair. It provides good pain relief to patients, but the function of the operated shoulder is less than it was pre-injury.
A research report submitted to the Faculty of Health Sciences, the University of Witwatersrand in partial fulfilment of the requirements for the Degree of Master of Medicine in the branch of Orthopaedic Surgery. Johannesburg, 2017
Keywords: Hemiarthroplasty Fractures Humerus